2019
DOI: 10.1002/jnr.24526
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between aging‐associated loss of protein homeostasis and extracellular vesicles in neurodegeneration

Abstract: The finding of an effective cure or treatment for neurodegenerative diseases is one of the biggest challenges for this century. Although these diseases show different clinical manifestations, the presence of toxic protein aggregates in the brain of patients is a common feature to all of them, suggesting a loss of protein homeostasis.Aging, the primary risk factor for the majority of neurodegenerative disorders, is linked to the impairment of degradative compartments such as lysosomes and autophagosomes. Beside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 268 publications
(295 reference statements)
0
11
0
Order By: Relevance
“…Involvement in cellular homeostasis Cells secrete exosomes in response to changes in their environmental conditions or to impairment of degradative compartments, thus enabling them to maintain their homeostasis and integrity (reviewed in [16,53,54]). Environmental conditions can drive membrane flux variations, in turn leading to changes in proteins incorporated in exosomal membranes [30].…”
Section: 312mentioning
confidence: 99%
“…Involvement in cellular homeostasis Cells secrete exosomes in response to changes in their environmental conditions or to impairment of degradative compartments, thus enabling them to maintain their homeostasis and integrity (reviewed in [16,53,54]). Environmental conditions can drive membrane flux variations, in turn leading to changes in proteins incorporated in exosomal membranes [30].…”
Section: 312mentioning
confidence: 99%
“…Emerging data strongly suggest that the extracellular secretion may also play an important role in the maintenance of intracellular protein homeostasis by cooperating with or even being a part of the PQC system (Desdín-Micó and Mittelbrunn, 2017 ; Xu et al, 2018 ; Guix, 2020 ). In fact, it has been found that several NDs-related proteins are secreted in double membrane spherical particles known as extracellular vesicles.…”
Section: The Protein Quality Control Systemmentioning
confidence: 99%
“…Although the causes and the cellular pathways leading to AD pathogenesis are not fully understood, the amyloid cascade hypothesis indicates the accumulation of amyloid β (Aβ) oligomers and fibrils as the main hallmark of AD. Aβ aggregates are very neurotoxic and cause severe damage to neurons; they are responsible for various phenomena, such as oxidation, lipid peroxidation, inflammation, disturbance of cell functions, apoptosis, and neurofibrillary tangles [ 24 , 25 , 26 , 27 , 28 , 29 ]. For these reasons, most AD therapeutic strategies are mainly centered on Aβ targeting, limiting the possibility to exploit new, potential AD treatments based on the implication of diverse mechanisms of AD etiology.…”
Section: Introductionmentioning
confidence: 99%